Engineering a Lactobacillus Lysine Riboswitch to Dynamically Control Metabolic Pathways for Lysine Production in Corynebacterium glutamicum - Qingwei Jiang; Feng Geng; Juan Shen; Ping Zhu; Zhaoxin Lu; Libang Zhou; Fengxia Lu (Microorganisms, 2024)
Knock-out of genes of metabolic pathways is conventionally used in the metabolic engineering of microorganisms, but it is not applicable for genes of essential pathways. In order to avoid undesirable effects caused by gene deletion, it is attractive to develop riboswitches to dynamically control the metabolic pathways of microbial cell factories. In this regard, the aim of this study is to utilize the lysine riboswitch to control gene expressions of the biosynthetic pathways and by-pathways and thus improve lysine production in Corynebacterium glutamicum. To achieve this, a natural lysine riboswitch from Lactobacillus plantarum (LPRS) was first detected and then fused with RFP to test its functionality. After that, engineered lysine-activated (Lys-A) and lysine-repressed (Lys-R) riboswitches were successfully screened by dual genetic selection. Furthermore, the optimized A263 and R152 were applied to control the expression of aspartate kinase III and homoserine dehydrogenase in the lysine-producing strain C. glutamicum QW45, respectively. In contrast with QW45, the growth of the resulting A263-lysC mutant QW48 was similar to that of QW45; however, the growth of the resulting R357-hom mutant QW54 was slightly inhibited, indicating an inhibition of threonine biosynthesis caused by the riboswitch upon binding of intracellular lysine. Importantly, the lysine production of QW48 and QW54 was, respectively, 35% and 43% higher than that of the parent strain QW45, implying more metabolic flux directed into the lysine synthesis pathway. Finally, the engineered A263 and R357 were simultaneously applied to the same mutant QW55, which greatly improved lysine production. Thus, the approach demonstrated in this work could be principally used as a powerful tool to dynamically control any other undesired metabolic pathways.